Lesson hub

## Can't find the answer? Try online tutoring

We have the UK’s best selection of online tutors, when and for how long you need them.

Getting 1-on-1 support is cheaper than you might think.

### Participating users

Welcome to our free-to-use Q&A hub, where students post questions and get help from other students and tutors.

You can ask your own question or look at similar Maths questions.

2x+13=(6x-30).2.4

2x+13=48x-240

253=46x

x=5.5

As the LHS equation is in the form ratio, move that 4 to RHS

2x+13=(6x-30).2.4

2x+13=48x-240

253=46x

x=5.5

Applying BODMAS  rule

(2x + 13)*4 = (6x-30)*2

8x + 52 = 12x -60;

taking variable to R.H.S

112 = 4x;

x = 112/4;

x = 28

multiplying out the brackets on both sides we get

8x+52=12x-60

bringing the xs to one side, we get:

112=4x

x = 28

2(2x+13)=4(6x-30)

4x+26=24x-120

120+26=24x-4x

146=20x

x=146/20

=7.3

(2x+13):4 =(6x-30):2

means (2x+13)/4 = (6x-30)/2

implies (2x+13)*2 =(6x-30)*4

implies 4x +26 = 24x - 120

implies 120+26 = 24x-4x

implies 20x = 146

implies x = 146/20 = 7.3

therefore x = 7.3

x=11/2

It requires explanation and i dont want to solve this question you will solve it using your own mind but i can give examples and explanation